2012
DOI: 10.3892/ol.2012.952
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant intraductal papillary mucinous neoplasm and neuroendocrine tumor of the pancreas

Abstract: Abstract. Intraductal papillary mucinous neoplasm (IPMN) and neuroendocrine tumor (NET) of the pancreas are rare tumors and their association is not expected to be frequent. However, certain studies have suggested that the concomitant occurence of these tumors may be more frequent than previously thought. In the current study, we describe a case of concomitant occurrence of IPMN and NET of the pancreas and review the clinicopathological features of previously published cases and the current one. A 68-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…Whereas neuroendocrine features are uncommon in IPMNs ( 44 ), these precancerous lesions can coexist with NETs in ~3-5% of cases (45)(46)(47), not dissimilar to the current series (2/31 IPMNs exhibited an elevated NETest). Th e latter is an interesting "false positive" as previous histopathological studies have indicated that IPMNs and NETs can occur in adjacent areas of the pancreas ( 48,49 ). Such lesions are rarely functional and have a relatively small size (~1.5 cm), raising the possibility that additive information from a blood biomarker test may be of some clinical utility.…”
Section: Discussionmentioning
confidence: 88%
“…Whereas neuroendocrine features are uncommon in IPMNs ( 44 ), these precancerous lesions can coexist with NETs in ~3-5% of cases (45)(46)(47), not dissimilar to the current series (2/31 IPMNs exhibited an elevated NETest). Th e latter is an interesting "false positive" as previous histopathological studies have indicated that IPMNs and NETs can occur in adjacent areas of the pancreas ( 48,49 ). Such lesions are rarely functional and have a relatively small size (~1.5 cm), raising the possibility that additive information from a blood biomarker test may be of some clinical utility.…”
Section: Discussionmentioning
confidence: 88%
“…97, 178181 Although neuroendocrine tumors can occur synchronously with IPMNs, it is much more common to see a non-neoplastic aggregation of the islets of Langerhans secondary to long-standing duct obstruction. 182185 This latter finding should not be over-diagnosed as “islet cell hyperplasia,” or as a neuroendocrine neoplasm.…”
Section: Resultsmentioning
confidence: 97%
“…1,2 The relatively common synchronous tumors in the pancreas are the combination of intraductal papillary mucinous neoplasm (IPMN) and NET. [10][11][12][13][14][15][16][17] Serous cystadenoma is occasionally found as a component of pancreatic synchronous tumors. [18][19][20][21][22] Only a few cases mentioned the constitution of an adenocarcinoma in synchronous pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%